1990
DOI: 10.1177/039139889001301105
|View full text |Cite
|
Sign up to set email alerts
|

Non-A, Non-B Hepatitis and Anti-HCV Antibodies in Dialysis Patients

Abstract: To define the prevalence of non-A, non-B hepatitis, antibodies to HCV were detected in 193 patients on renal replacement therapy (52 transplant and 141 hemodialysis patients) and in 50 staff members of a Nephrology Department. Unequivocal seroconversion was documented in 5 transplant (9.6%) and in 26 dialysis patients (18.4%). In the dialysis population, the prevalence of anti-HCV antibodies was evaluated in patients grouped according to the number of blood transfusions and to the different sections of dialyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
6

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 9 publications
2
34
0
6
Order By: Relevance
“…The risk of acquiring the infection by HCV in dialysis is well known and the higher the dialysis duration, the higher the seropositivity risk for hepatitis C [1,4,5]. In this study performed in Tubarao, Santa Catarina State, we found a direct association between the dialysis duration and the seropositivity for hepatitis C (p < 0,001), what corroborate with the idea that the long-term dialysis treatment involving hospital procedures may contribute with the infection dissemination [22].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The risk of acquiring the infection by HCV in dialysis is well known and the higher the dialysis duration, the higher the seropositivity risk for hepatitis C [1,4,5]. In this study performed in Tubarao, Santa Catarina State, we found a direct association between the dialysis duration and the seropositivity for hepatitis C (p < 0,001), what corroborate with the idea that the long-term dialysis treatment involving hospital procedures may contribute with the infection dissemination [22].…”
Section: Discussionsupporting
confidence: 84%
“…The increase of prevalence varies from an average of 12% of patients under dialytic treatment for less than five years to 37% of patients under treatment for more than five years [3]. The higher the time of dialysis, the more the seropositivity prevalence for the Hepatitis virus [1,4,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Possivelmente, houve um fator de confusão, já que, por algum tempo essa foi a modalidade de trataTabela 3 -Associação não ajustada entre potenciais fatores de risco relacionados às clínicas de hemodiálise e à positividade sorológica para hepatite C. A média de tempo de hemodiálise foi maior nos pacientes reagentes para o anti-VHC, como já constatado por outros estudos. 4,5,10 Parece lógico pensar que um paciente há mais tempo em tratamento dialítico esteja mais sujeito a acidentes com potencial de contaminação e tenha maior chance de ser transfundido. Porém, a associação entre tempo de diá-lise e positividade para anti-VHC pode não depender exclusivamente de transfusões sanguíneas.…”
Section: Variáveisunclassified
“…Sabe-se que no País esse procedimento é uma constante nas unidades de diálise. Da mesma forma, o compartilhamento do frasco de heparina já foi sugerido como possível veículo de disseminação de hepatite C. 10 No presente estudo, o preparo prévio de heparina na seringa antes de manusear o paciente mostrou associação com menor prevalência de anti-VHC.…”
Section: 21unclassified